The ethics of architecture - Kingwell, Mark 1963- (Oxford University Press, 2020)
The Ethics of Architecture offers a short and approachable scholarly introduction to a timely question: in a world of increasing population density, how does one construct habitable spaces that promote social goals like health, happiness, environmental friendliness, and justice? What are the special ethical obligations assumed by architects? Because their work creates the basic material conditions that make all other human activity possible, architects and their associates in building enjoy vast influence on how all we live, work, play, worship, and think. With this influence comes tremendous, and not always examined, responsibility. This book addresses the range of ethical issues that architects face, with a broad understanding of ethics. Beyond strictly professional duties - transparency, technical competence, fair trading - lie more profound issues that move into aesthetic, political, and existential realms. Does an architect have a duty to create art, if not always beautiful art? Should an architect feel obliged to serve a community and not simply the client? Is social justice a possible orientation for architectural practice? Is there such a thing as feeling compelled to "shelter being" in architectural work? By taking these usually abstract questions into the region of physical creation, the book attempts a concrete reformulation of "architectural ethics" as a matter of deep reflection on the architect's role as both citizen and caretaker. Thinkers and makers discussed include Le Corbusier, Martin Heidegger, Lewis Mumford, Rem Koolhaas, Jane Jacobs, Arthur Danto, and John Rawls. An added preface addresses architectural issues arising during and after the 2020 COVID-19 pandemic"--